A breakthrough biosorbent in removing heavy metals: Equilibrium, kinetic, thermodynamic and mechanism analyses in a lab-scale study - Abdolali, Atefeh (2023)
A breakthrough biosorbent namely multi-metal binding biosorbent (MMBB) made from a combination of tea wastes, maple leaves and mandarin peels, was prepared to evaluate their biosorptive potential for removal of Cd(II), Cu(II), Pb(II) and Zn(II) from multi-metal aqueous solutions. FTIR and SEM were conducted, before and after biosorption, to explore the intensity and position of the available functional groups and changes in adsorbent surface morphology. Carboxylic, hydroxyl and amine groups were found to be the principal functional groups for the sorption of metals. MMBB exhibited best performance at pH5.5 with maximum sorption capacities of 31.73, 41.06, 76.25 and 26.63mg/g for Cd(II), Cu(II), Pb(II) and Zn(II), respectively. Pseudo-first and pseudo-second-order models represented the kinetic experimental data in different initial metal concentrations very well. Among two-parameter adsorption isotherm models, the Langmuir equation gave a better fit of the equilibrium data. For Cu(II) and Zn(II), the Khan isotherm describes better biosorption conditions while for Cd(II) and Pb(II), the Sips model was found to provide the best correlation of the biosorption equilibrium data. The calculated thermodynamic parameters indicated feasible, spontaneous and exothermic biosorption process. Overall, this novel MMBB can effectively be utilized as an adsorbent to remove heavy metal ions from aqueous solutions.